Green tea improves cognitive function through reducing AD-pathology and improving anti-oxidative stress capacity in Chinese middle-aged and elderly people - Zhang, Ran; Zhang, Lei; Li, Zeng; Zhang, Ping; Song, Hao; Yao, Dong-ai; Cao, Jing; Zhang, Jun-jian (Frontiers in Aging Neuroscience, 2022)
Background: Numerous benefits of green tea have been reported. However, the effects of green tea on cognitive function remain disputable and the mechanism is still unclear. Objective: To investigate the relationship of green tea consumption with cognitive function and related blood biomarkers among Chinese middle-aged and elderly people. Methods: 264 participants aged 50-70 years old were enrolled from Zhongnan Hospital of Wuhan University. They were interviewed about green tea consumption patterns and underwent neuropsychological tests covering five main cognitive domains to assess cognition including Montreal Cognitive Assessment (MoCA) and the other 10 scales. Then we detected serum oxidative stress biomarkers including Superoxide Dismutase (SOD), Malondialdehyde (MDA), Glutathione Peroxidase (GPx), Glutathione Reductase (GR) and Alzheimer's disease (AD) markers including β-amyloid (Aβ)40, Aβ42 and phosphorylated tau-181 (pTau181). Results: In the tea-consumption group, the MoCA scores (P=0.000), Hopkins Verbal Learning Test immediate recall (P=0.012) and delayed recall (P=0.013) were significantly higher while Trail Making Test-B (P=0.005) and Victoria Stroop test interference (P=0.000) were lower. In terms of oxidative stress markers, the tea-consumption group had lower serum MDA levels (P=0.002) and higher serum SOD (P=0.005) and GPx (P=0.007) levels. In terms of AD markers, serum pTau181 (P＜0.000), Aβ42 (P=0.019) and total Aβ levels (P=0.034), but not serum Aβ40 levels, were lower in the tea-consumption group. In the logistic regression analysis, there was a significant negative correlation between green tea consumption and cognitive impairment (OR=0.26, 95%CI 0.13 0.52 for high group). Conclusion: Regular green tea consumption is associated with better cognitive function among Chinese middle-aged and elderly people, mainly reflected in memory and executive function. It may achieve protective effects by reducing AD-related pathology and improving anti-oxidative stress capacity and higher levels of tea consumption have a stronger protective effect.